Ban the Box measures help high-crime neighborhoods - Stan Veuger; Daniel Shoag (American Enterprise Institute (AEI), 2020)
A sizable number of localities have in recent years limited the use of criminal background checks in hiring decisions, or "banned the box." Using LEHD Origin-Destination Employment and American Community Survey data, we show that these bans increased employment of residents in high-crime neighborhoods by as much as 4%. These increases are particularly large in the public sector. At the same time, we establish using job postings data that employers respond to ban-the-box measures by raising experience requirements. A perhaps unintended consequence of this is that women, who are less likely to be convicted of crimes, see their employment opportunities reduced.
Keywords: A; 330; Labor economics; Prison Education and Reentry